Proceedings of the 42nd Annual Southeast Regional Conference 2004
DOI: 10.1145/986537.986601
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of cache replacement policies for the SPEC CPU2000 benchmark suite

Abstract: Replacement policy, one of the key factors determining the effectiveness of a cache, becomes even more important with latest technological trends toward highly associative caches. The state-of-the-art processors employ various policies such as Random, Least Recently Used (LRU), Round-Robin, and PLRU (Pseudo LRU), indicating that there is no common wisdom about the best one. Optimal yet unattainable policy would replace cache memory block whose next reference is the farthest away in the future, among all memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 8 publications
(13 reference statements)
0
73
0
Order By: Relevance
“…Most of the time, solutions aim to improve or adapt the replacement policy needed by the demand-paging strategy because researches [18] showed that a gap always exists up to the theoretical best one, known as MIN [19]. When a cache is full and when the CPU tries to read instructions not already present in cache, the new page loaded from the NAND must overwrite an existing one in the cache.…”
Section: Motivation Around Smart-card and Flash-memories Characteristicsmentioning
confidence: 99%
“…Most of the time, solutions aim to improve or adapt the replacement policy needed by the demand-paging strategy because researches [18] showed that a gap always exists up to the theoretical best one, known as MIN [19]. When a cache is full and when the CPU tries to read instructions not already present in cache, the new page loaded from the NAND must overwrite an existing one in the cache.…”
Section: Motivation Around Smart-card and Flash-memories Characteristicsmentioning
confidence: 99%
“…The first source of inaccuracy can be completely eliminated if one is willing to spend additional space to store one stack histogram per cache set. But this is unlikely to allow for great improvements in the precision of predicted miss ratios [1]. The second source has a greater impact on the quality of predictions, but is more difficult to eliminate.…”
Section: Accuracy Of Stack Histogramsmentioning
confidence: 99%
“…its state space and transitions. First we need [3,4,1,0] hist: [5] [0, 4 FIFO, history length 1, cutoff age 5) showing some transitions and how probabilities are assigned to them. The value above an arrow is the transition probability.…”
Section: Model Constructionmentioning
confidence: 99%
See 2 more Smart Citations